“How the Motherland Begins”: on Development of Song’s Patriotic Semantics - V. N. Levina; K. Van (Научный диалог, 2018)
The question of development of patriotic semantics in a song is considered taking into account genre approach. Attention is paid to text units that actualize patriotic semantics in the song context. The article presents the results of functional and semantic analysis of the text of the song “How the Motherland Begins.” The authors claim that in the text semantic field of this song three levels of patriotic semantics are actualized. Text units specific for each level are characterized. The novelty of the study is seen in the fact that the features of the development of patriotic semantics in the communicative space of the song text are analyzed using the concept of “text units.” The relevance of the study is due to the demand for songs as an empirical material in the modern scientific paradigm, as well as the implementation of one of the main functions of the language - accumulative, that is, the function of accumulation and storage of information, historical and cultural memory, transfer of value orientations to the next generations. It is emphasized that the reference to the theme of patriotism is of great social importance in the practice of teaching Russian as a native, non-native and foreign language. The authors use the terms text landscape unit and text unit with patriotic semantics and develop their content. In the course of the functional-semantic analysis of song text, the initial and potential, incremented content of text units is revealed, taking into account the context environment.